Breach of Proper Notice Regarding Arbitrator Appointment or Arbitration Proceedings as Grounds for Refusal of Enforcement Under the New York Convention - Candan Yasan Tepetaş (Public and Private International Law Bulletin)
The right to be heard is a fundamental right granted to parties in arbitration proceedings, and a requirement of the right to be heard is that the parties must be adequately and timely informed about the appointment of the arbitrator and the arbitral proceedings. Proper notice ensures the implementation of the right to be heard in arbitration. Thus, notice directly affects the validity and enforcement of arbitral awards. Article V(1)(b) of the United Nations (UN) Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York Convention; UN, June 10, 1958) provides that recognition or enforcement of an award may be refused if “the party against whom the award is invoked was not given proper notice of the appointment of the arbitrator or the arbitration proceedings.” This study examines what should be understood from the concept of “proper notice” under Article V(1)(b) of the New York Convention and how this conceptis elaborated upon in the practice of arbitration. The study in this respect first discusses the right to be heard in arbitration and the relationship between this right and proper notice. The study then goes on to evaluate the elements required for a notice to be deemed proper. Subsequently, the article examines the issues related to the application of Article V(1)(b) of the New York Convention, such as applicable law and burden of proof, and finishes up with the conclusion. The facts that notices in arbitration proceedings are not made by official means and that the methods in international agreements are not applied do not cause a notice to be deemed improper. Moreover, not every breach or deficiency in presenting a notice will result in a refusal to enforce an award under Article V(1)(b) of the New York Convention. Under Article V(1)(b) of the New York Convention, objections regarding violations of the right to be heard due to a lack of proper notice should be interpreted narrowly and should be of a nature that may affect the outcome of the arbitration proceedings. Finally, even if the content of the notice is not written on the tracking documents a courier company issues, these documents should be deemed sufficient to prove that a notice has been made. If the respondent claims that the notices made by cargo or courier are unrelated to the arbitration proceedings, the respondent needs to prove this.